PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI BKD KOTA MAKASSAR - Mansur Amirullah (Jurnal Bisnis dan Kewirausahaan, 2019)
The objective of this research were (1) to find out and analyze the influence of competency toward performance of Regional Officer Agency Staff in Makassar City; (2) to find out and analyze the influence of job environment toward performance of Regional Officer Agency Staff in Makassar City. This research was conducted in Regional Officer Agency at Makassar City. This using census population method. There were 65 respondents taken out of all staffs. The data obtained to reveal the respondents’ features and research description were analyzed descriptively, meanwhile, multiple regression analysis was used to investigate the quantitative data. SPSS v16 software was used. The results showed that (1) human resource competency had positive and significant effect toward performance of civil servant at Regional Officer Agency Staff in Makassar City; (2) job environment had negative effect toward performance of civil servant at Regional Officer Agency Staff in Makassar City.